THE IMPLEMENTATION PICTURE AND PICTURE STRATEGY TO INCREASE STUDENTS' ABILITY IN VOCABULARY AT MAN 3 MEDAN - Gumarpi Rahis Pasaribu; Sholihatul Hamidah Daulay; Zainuddin Saragih (PRIMACY Journal of English Education and Literacy, 2023)
This research was intended to find out the empirical evidence of students’ ability in vocabulary by using picture and picture strategy in class X of Man 3 Medan. The method used in this research was Classroom Action Research (CAR) method in which to identify and to solve the problem on the students’ ability in vocabulary. The result of the data analyzing showed that there was an increasing on the students’ ability in vocabulary through picture and picture strategy. It was showed from the mean of pre – test was 31,62. After picture and picture strategy was applied in the first cycle there was an increase of the students’ mean score which was 53,22 and for the second cycle after reflection on the first cycle, there was an increase of students mean score which 92,25. Moreover, post – test I session which was 19,35% (6 students) who got point of 70. In post – test II for the second cycle which was 90,32 % (28 students) who got the point of over 70. It was found that the teaching vocabulary by picture and picture strategy could increase the students’ ability in vocabulary.